Two color imaging of different hypoxia levels in cancer cells - Wallabregue, ALD; Bolland, H; Faulkner, S; Hammond, EM; Conway, SJ (American Chemical Society, 2023)
Hypoxia (low oxygen levels) occurs in a range of biological contexts, including plants, bacterial biofilms, and solid tumors; it elicits responses from these biological systems that impact their survival. For example, conditions of low oxygen make treating tumors more difficult and have a negative impact on patient prognosis. Therefore, chemical probes that enable the study of biological hypoxia are valuable tools to increase the understanding of disease-related conditions that involve low oxygen levels, ultimately leading to improved diagnosis and treatment. While small-molecule hypoxia-sensing probes exist, the majority of these image only very severe hypoxia (<1% O2) and therefore do not give a full picture of heterogeneous biological hypoxia. Commonly used antibody-based imaging tools for hypoxia are less convenient than small molecules, as secondary detection steps involving immunostaining are required. Here, we report the synthesis, electrochemical properties, photophysical analysis, and biological validation of a range of indolequinone-based bioreductive fluorescent probes. We show that these compounds image different levels of hypoxia in 2D and 3D cell cultures. The resorufin-based probe 2 was activated in conditions of 4% O2 and lower, while the Me-Tokyo Green-based probe 4 was only activated in severe hypoxia─0.5% O2 and less. Simultaneous application of these compounds in spheroids revealed that compound 2 images similar levels of hypoxia to pimonidazole, while compound 4 images more extreme hypoxia in a manner analogous to EF5. Compounds 2 and 4 are therefore useful tools to study hypoxia in a cellular setting and represent convenient alternatives to antibody-based imaging approaches.